Differentiation and correlation of regional uptake heterogeneity with cardiac dysfunction in biopsy-proven transthyretin amyloid cardiomyopathy using quantitative single-photon emission computed tomography/computed tomography: a single-center, cross-sectional study - Masakazu Tsujimoto; Hideki Kawai; Shingo Tanahashi; Masayoshi Sarai; Yasuki Asada; Hideo Izawa (EJNMMI Research)
Abstract Background Cardiac amyloidosis requires quantitative assessment using technetium-99m pyrophosphate (99mTc-PYP) single-photon emission computed tomography (SPECT)/computed tomography (CT) for adequate discrimination and evaluation of disease extent. This study aimed to evaluate the utility of standardized uptake value (SUV) analysis using 99mTc-PYP SPECT/CT in pathologically-confirmed transthyretin amyloid cardiomyopathy (ATTR-CM). The study also explored the relationship between local uptake heterogeneity and indicators of cardiac impairment. Methods Forty patients diagnosed via heart biopsy and genetic analysis (20 ATTR-CM; 4 light-chain amyloidosis, 16 non-amyloidosis) were enrolled. The mean SUVs of the heart and aorta were measured using SPECT images. Discrimination performance was evaluated by comparing each SUV, the heart-to-aorta ratio (rSUVH/Ao), and the heart-to-contralateral-lung ratio with pathological findings serving as the gold standard. Polar maps were analyzed to assess local SUV distribution in patients with ATTR-CM. The coefficient of variation (COV) of myocardial uptake, difference score between the septum and lateral wall (%DS), base-to-apex variability, and total cardiac SUV were calculated and compared with echocardiographic parameters. Results All metrics were significantly different between the ATTR-CM and non-amyloidosis groups. The rSUVH/Ao effectively differentiated patients with ATTR-CM from those with light-chain or non-amyloidosis. Local myocardial SUV distribution correlated with impaired cardiac function. Notably, COV showed significant correlations with e' (R = 0.782) and E/e' (R =  − 0.625), linking heterogeneity to myocardial stiffness and diastolic dysfunction. Larger %DS, which predominantly reflected the ATTR-CM pattern of high septal uptake, correlated significantly with thinner walls (average wall thickness, R =  − 0.655; relative wall thickness, R =  − 0.486). As the total cardiac SUV increased, the %DS decreased (reflecting more homogeneous distribution), and global longitudinal strain worsened (R = 0.614). These observations indicated that greater impairment was associated with a higher disease burden. Conclusions This study demonstrated that quantitative SPECT analysis provides a valuable tool for the diagnostic evaluation and differentiation of ATTR-CM. The rSUVH/Ao offers high discriminatory performance. Local heterogeneity and total myocardial uptake are closely related to the disease burden and extent, as reflected by structural and functional abnormalities on echocardiography. These findings suggest potential relevance to the non-invasive assessment of these aspects of the disease at a single time point. Graphical abstract